Self-determination anxiety and signs of crisis — fragmentation, performativity, postdramatic - Bašović, Almir (Amfiteater (Ljubljana), 2022)
The text will address some issues that substantially determine contemporary thinking about European drama and theatre. Thus, for example, the idea of fragmentary dramaturgy will be considered in relation to the first case of such writing, namely, the comedies of Aristophanes. The fundamental questions that should be taken into consideration are the following: relative to what idea of the “whole” (or “totality”) is a certain dramatic work fragmented, and according to what logic are these fragments connected to a certain unified “whole”? Another important aspect refers to our belief that we live in an exclusive moment in history and that performativity is a distinguishing characteristic of our time. This assumption seems to be neglecting the long-standing tradition, dating back to Plato, which considered spoken language as an act in itself.
Keywords: Fischer-Lichte, Erika; fragmentacija; fragmentation; Hacke, Gustav René; Lehmann, Hans-Thies; manierizem; mannersim; Müller, Heiner; performativity; performativnost; postdramatic theatre; postdramsko gledališče